Pengaruh Stres Kerja, Kompetensi dan Lingkungan Kerja Terhadap Kinerja Karyawan Pt Lion Air Bandara Kualanamu - M Masdiyanto; Sjahril Effendy; Muis Fauzi Rambe (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2023)
The research uses an associative quantitative approach. The sampling technique used was saturated sampling technique as many as 46 people. Hypothesis testing is done by distributing questionnaires. Then the questionnaire data was tested using the SPSS 26 application by testing the validity, reliability, heteroscedasticity, and multicollinearity tests. The data analysis technique used is multiple linear regression, t test (partial), F test (simultaneous) and R square test. From the test results that have been obtained, it can be concluded that partially work stress has a positive and significant effect on performance, competence has a positive and significant effect on performance, work environment has a positive and significant effect on employee performance. Then simultaneously work stress, competence and work environment have a positive and significant effect on performance